EVALUASI PENERAPAN ISO 9001:2008 DI LINGKUNGAN UIN SYARIF HIDAYATULLAH JAKARTA - Amirudin Amirudin (ETIKONOMI, 2014)
The aim of this research is to evaluate the ISO 9001: 2008 implementation in UIN Syarif Hidayatullah Jakarta. The assumption that used on this research is the ISO: 9001: 2008 implementation still can’t give an impact to service quality. This research used the survey technique such as quetionnaire. The analysis method that used is descriptive analysis, inferential analysis, and question analysis. The result from this research is there were influences of ISO 9001: 2008 implementation on employee performance at UIN Syarif Hidayatullah Jakarta, and also as average from eight dimensions on ISO 9001: 2008 had a good category. In some category, students still non satisfied on employee performanceDOI: 10.15408/etk.v13i1.1877